Konsepsi Implementasi Sistem Informasi Managemen dalam Mendukung Pelayanan Tenaga Pendidik - Ali Mustofa; Andi Prayoga (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2020)
The use of management information systems in the field of education (SIMDIK) is very important in management, both in terms of managing academic administration, staffing administration, administration of facilities and infrastructure, reporting administration and so on. However, managing the administrative staff is more prioritized in educational institutions, especially teaching staff because they are the most important element in the education process. The use of management information system as a service system for teaching and education staff will be managed and empowered through SIMPATIKA (Information System for Educators and Education Personnel of the Ministry of Religion). It is helpful the management of teaching and educational staff, although some weaknesses in it. SIM is not only necessary but it is used to realize the vision, improve the educators and educational staff quality in accordance with the educators and education standards. So the use of SIM is as a mandatory step to carry out its mission. SIM maintenance should be prioritized to serve educators and education staff so it realizes the educators and educational staff quality in accordance with the educators and education standards.